Pelatihan Manajemen Keuangan Syariah untuk Guru dan Murid di MI Arrazaq Islamic School Rumbai Pekanbaru: Sharia Financial Management Training for Teachers and Students at MI Arrazaq Islamic School Rumbai Pekanbaru - Yetti, Febri Delmi; Syamsul Rizal (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this community service is to improve literacy and sharia financial management skills for teachers and students at MI Arrazaq Islamic School Rumbai Pekanbaru through applicable and contextual training based on Islamic values. This community service uses the ABCD (Asset-Based Community Development) approach to empower teachers and students of MI Arrazaq Islamic School in managing sharia finances based on community potential. The activities are carried out through four stages: Discovery (identification of school assets), Dream (formulation of shared ideals), Design (preparation of two-day training for teachers and students), and Destiny/Delivery (implementation of training and follow-up). As a result, the training was effective and resulted in a sustainability plan such as the formation of sharia financial ambassadors and sharia-based student cooperatives. The results of the training program showed that the ABCD approach was effective in exploring and empowering school community assets. The training succeeded in increasing teachers' and students' understanding of the principles of sharia finance in an applicable manner. The formation of the Sharia Financial Ambassador Team and the plan for a sharia-based mini cooperative are real manifestations of the sustainability of the program. Overall, this program is able to form an Islamic economic culture that is integrated into learning and daily life at school.